Properties and Indicators of Ethical Propositions in Quran and Hadith - Mohammad Ja’far Sadri; Mahmud Rajabi (اخلاق وحیانی, 2016)
In Islamic ethical propositions, ethical orders signify the desirability of their subjects and their positive or negative relation to happiness, but in the ethical propositions included in Quran and Hadith there is hardly any instance of these concepts. In the present study, desirability is recognized as an important indicator of Islamic ethical propositions and the following reasons are presented for supporting this claim: “inclusion of near or remote affairs from the final end”, “inclusion of bidding and forbidding”, “indicating love and hatred”, “inclusion of the report of the practical manner of religious saints”, “inclusion of the promise of the reward or punishment”, “inclusion of positive or negative patterns”, “inclusion of admiration or condemnation of some actions and characteristics”, “expressing concern about some actions and characteristics”, “attribution of obligation or prohibition to some actions”.